Implementasi Model Problem Based Learning (PBL) Berbantuan Video Interaktif untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis Peserta Didik Kelas X - Herlin Anisa Sya'bani; Juariah; Riva Lesta Ariany (Mataram University, 2026)
Mathematical problem solving ability remains a challenge for many students, requiring more engaging learning approaches. This study examined differences in the mathematical problem-solving abilities of Grade 10 students after the implementation of the Problem Based Learning (PBL) model assisted by interactive videos. A quantitative pre-experimental method with a One Group Pretest Posttest Design was employed. The participants were 46 Grade 10 students from a senior high school in Bandung Regency. Data were collected using a validated and reliable essay test administered before and after the intervention. The data were analyzed using the Shapiro Wilk normality test and a paired-sample t-test. The mean pretest score increased from 11.35 to 32.22 out of a maximum score of 50. Statistical analysis revealed a significant improvement in students’ mathematical problem solving abilities after the implementation of the interactive video-assisted PBL model. The findings indicate that integrating interactive videos with PBL can effectively enhance students mathematical problemsolving abilities.